Research advances and gaps in marine planning: towards a global database in systematic conservation planning. (November 2018) - Álvarez-Romero, Jorge G.; Mills, Morena; Adams, Vanessa M.; Gurney, Georgina G.; Pressey, Robert L.; Weeks, Rebecca; Ban, Natalie C.; Cheok, Jessica; Davies, Tammy E.; Day, Jon C.; Hamel, Mélanie A.; Leslie, Heather M.; et al.
Abstract: Systematic conservation planning (SCP) has increasingly been used to prioritize conservation actions, including the design of new protected areas to achieve conservation objectives. Over the last 10 years, the number of marine SCP studies has increased exponentially, yet there is no structured or reliable way to find information on methods, trends, and progress. The rapid growth in methods and marine applications warrants an updated analysis of the literature, as well as reflection on the need for continuous and systematic documentation of SCP exercises in general. To address these gaps, we developed a database to document SCP exercises and populated it with 155 marine SCP exercises found in the primary literature. Based on our review, we provide an update on global advances and trends in marine SCP literature. We found accelerating growth in the number of studies over the past decade, with increasing consideration of socioeconomic variables, land-sea planning, and ecological connectivity. While several studies aimed to inform conservation decisions, we found little evidence of input from practitioners. There are important gaps in geographic coverage and little correspondence with areas most threatened. Five countries lead most studies, but their networks suggest potential for capacity building through collaborations. The varying quality and detail in documentation of studies confirmed the limited opportunities to develop and assess the application of best practice in conservation planning. A global database to track the development, implementation, and impact of SCP applications can thus provide numerous benefits. Our database constitutes an important step towards the development of a centralized repository of information on planning exercises and can serve several roles to advance SCP theory and practice: it facilitates assessing geographic coverage and gaps; scientists and practitioners can access information to identify trends in the use of data, methods, and tools; reviewers and editors of journals can assess whether studies have covered important literature and developments; donors and non-government organizations can identify regions needing further work; and practitioners and policy-makers can learn from previous plans. Highlights: The number of marine conservation planning studies is growing exponentially. Socioeconomics, land-sea planning and connectivity are current key research areas. Studies have limited geographic coverage and correspondence with threatened areas. A few countries with extensive international collaboration networks lead marine SCP. A global database to track development, implementation and impact of SCP is needed.